2018
DOI: 10.1515/jelf-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

“Cool my doubt is erased”: constructive disagreement and creating a psychologically safe space in multicultural student teamwork

Abstract: This paper investigates the roles of disagreement and trust in multicultural teamwork on an English-medium master’s programme at an Austrian business university. The teamwork project – assigned by the content teacher – took place mostly outside the classroom and simulated business practice both in terms of the tasks and the multicultural context. Each team comprised two Austrian students and two international students, resulting in an English as a lingua franca (ELF) setting. The teams were observed and audio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Toomaneejinda & Harding (2018) showed that participants in ELF academic group discussion used a wide range of strategies to express disagreement, including shift of focus, turn-management practices and use of gaze. Komori-Glatz (2018) demonstrated that high levels of trust supported the ability to disagree and challenge one another. Additionally, joking, talking about shared interests, exploring others' cultural background and "letting pass" strategies (Firth, 1996), the latter describing instances in which inaccurate language use is not flagged up, facilitate intercultural team work in HE (Komori-Glatz, 2017).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Toomaneejinda & Harding (2018) showed that participants in ELF academic group discussion used a wide range of strategies to express disagreement, including shift of focus, turn-management practices and use of gaze. Komori-Glatz (2018) demonstrated that high levels of trust supported the ability to disagree and challenge one another. Additionally, joking, talking about shared interests, exploring others' cultural background and "letting pass" strategies (Firth, 1996), the latter describing instances in which inaccurate language use is not flagged up, facilitate intercultural team work in HE (Komori-Glatz, 2017).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Supporting also means being forgiving of mistakes and disagreeing constructively (Komori-Glatz, 2018; C. E. Larson & Lafasto, 1989). Critically Evaluating Collaboration requires a willingness to disagree (Andrews & Rapp, 2015;Komori-Glatz, 2018;Nussbaum, 2008). This may involve identifying gaps in logic, improving upon others' ideas, and offering alternative perspectives and possibilities, while still remaining respectful and open-minded.…”
Section: Supportingmentioning
confidence: 99%
“…The majority of studies on ELF disagreement acts were conducted in an academic setting (e.g., Bjørge, 2012;Komori-Glatz, 2018;Matsumoto, 2018;Toomaneejinda & Harding, 2018). One main study is by Bjørge (2012), who followed a comparative approach by comparing the linguistic forms for disagreeing found in business English textbooks and the ones used by international students in simulated negotiations.…”
Section: Previous Studies On Elf Disagreementmentioning
confidence: 99%
“…While much of the early research on ELF interaction mostly focused on such cooperative aspects, more recently, other questions have been raised concerning ELF users' disagreement practices. In particular, ways of expressing conflicting opinions in ELF interactions have been investigated in academic settings (Bjørge, 2012;Komori-Glatz, 2018;Matsumoto, 2018;Toomaneejinda & Harding, 2018), informal settings (Jenks, 2012;Konakahara, 2015Konakahara, , 2017, with little attention to professional business contexts (Marra, 2016). Consequently, little is known about how ELF users display disagreement in real-life business contexts.…”
Section: Introductionmentioning
confidence: 99%